Mediating roles of perceived social support and sense of security in the relationship between negative life events and life satisfaction among left-behind children: A cross-sectional study - Liu, Na; Li, Xinzheng; Ding, Xuemei; Liu, Haixia; Zhang, Xiaoli (Frontiers in Psychology, 2023)
Objective Life satisfaction is closely related to the quality of life. Previous studies showed that left-behind children have low life satisfaction levels due to their separation from their parents. Therefore, it is significant to explore the risk factors and protective factors of left-behind children’s life satisfaction to improve their life quality. Therefore, the purpose of this study was to determine the mediating roles of perceived social support and sense of security in the relationship between negative life events and life satisfaction among left-behind children. Methods A survey was conducted on 281 left-behind children in rural Shandong, China using negative life events, perceived social support, a sense of security, and life satisfaction scales. Results Negative life events had a negative impact on life satisfaction (β = −0.34, p = 0.001). In addition, not only does social support mediate between negative life events and life satisfaction (β = −0.21, p = 0.001), but also in between, security (β = −0.05, p = 0.030). Moreover, social support and security act as a chain intermediary between negative life events and life satisfaction (β = −0.03, p = 0.010), with an indirect effect share of 4.76%. Conclusion Negative life events could directly or indirectly affect the life satisfaction of left-behind children through the chain-mediating effects of perceived social support or the sense of security alone. Perceived social support and the sense of security are two important targets for further improving the life satisfaction of LBC.